A lean case study on managing interlibrary loan and document delivery service in an academic library - Hasniza Amno; Nurulhuda Abdul Jais; Mustaqeem Abdullah; Bakiah Shaharuddin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Introduction: Interlibrary loan and document delivery (ILL/DD) is an essential service provided by academic libraries to support research activities, publication and academic programmes. ILL/DD service capitalises on resource sharing or library networking by providing library materials that are not available at the host library. The Lean Six Sigma method was applied to identify the root problems. A construction of a web-based system branded as “Request Book and Article System (RBAS)” soon followed as an intervention. A retrospective study was conducted from March 2020 to August 2021 (16 months) to evaluate the key indicators of the service. Customer feedback on service quality was also surveyed. The majority of request was for articles, 649 (87.5%), followed by book request 84 (11.3%) and ebook, 9 (1.2%). Turnaround time fell within 24 hours for the majority of requests, 494 (68.4%). The highest number was from article request category, 460 (71.8%). A high proportion of users (78%) deemed the service as “high quality”. The use of a lean approach and the development of a homegrown system have improved the ILL/DD service at our library. Here we share lean practices in ILL/DD management, focusing on transforming a manual method to a digital homegrown system development and its advantages.